PENGARUH IKLAN OBAT FLU DI TELEVISI TERHADAP PERILAKU SWAMEDIKASI - Mardiati, Nurul; Islamiyah, Robiatul; Fitriah, Rahmayanti (Jurnal Riset Kefarmasian Indonesia, 2021)
The high prevalence of flu and the easy availability of drugs in the market and at relatively affordable prices are one of the driving forces for self-medicating by the community. In addition, increasingly sophisticated technological advances make it easy for people to get information, one of which is drug advertisements on television that can influence consumer behavior in the selection of drugs used in self-medication. This research was conducted with the aim of knowing the effect of cold medicine advertisements on television on self-medication behavior in the community of Karang Intan District. This research method is a descriptive observational study with a cross sectional design. The sampling technique was carried out using non-random sampling method, namely accidental sampling, and the number of respondents was 100 people. The data collected comes from questionnaire data, which is filled in by respondents accompanied by researchers. Descriptive data analysis was performed by using the chi square test. The results showed that the effect of cold medicine advertisements on television on self-medicated behavior in the community of Karang Intan District has a significant p value of 0.000. The conclusion is that the advertisement of cold medicine on television has an influence on self-medication behavior in the community of Karang Intan District.